Fueling Time Mastery: How Self-Regulation Drives Time Management Through the Power of Grit in Vocational Teachers? - Babby Hasmayni; Khatrine Bartha; Mariah Kibtiyah (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Teachers at vocational high schools often struggle to manage their time effectively due to heavy workloads and diverse responsibilities. This study investigates the effect of self-regulation on time management, with grit as a mediating variable. Self-regulation refers to the ability to control behavior, set goals, and maintain focus, while grit reflects persistence and passion for long-term goals. Using a quantitative ex-post facto design, data were collected from 92 SMK teachers through total sampling. Three psychological scales were used: the self-regulation scale, the grit-short scale, and the time management scale. Data analysis employed descriptive statistics and mediation analysis using PROCESS Macro (Model 4) in SPSS 25. Results show that self-regulation has a positive and significant effect on time management through grit, which serves as a full mediator. This means self-regulation enhances time management only when accompanied by high levels of grit. The findings highlight the need to foster both self-regulation and grit in teacher development programs. Keywords: grit, self-regulation, teachers, time management, vocational high schools